Prevalence of depression and associated factors among HIV/AIDS Patients on HAART in Okugu Refugee Camp, Gambella, Ethiopia - Asefa, Adane; Hirpesa, Belay; Asaye, Zufan; Shifera, Nigusie; Sheferaw, Wegayehu Enbeyle; Mesafint, Gebremeskel (Frontiers in Psychiatry, 2025)
BackgroundDepression and HIV/AIDS are common mental health problems in people living in refugee camps under stressful conditions. When both conditions occur together in an already vulnerable population living in a deprived situation, they lead to severe health outcomes and complicate patient care. However, there is a shortage of data on the magnitude of depression and related factors among displaced populations living with HIV/AIDS in refugee camps. Therefore, this study aimed to assess the prevalence and factors associated with depression among HIV/AIDS patients living in the Okugu Refugee Camp, Ethiopia.MethodsA health facility-based cross-sectional study was conducted among a sample of 382 adults living with HIV/AIDS who were on highly active antiretroviral therapy (HAART) at the Okugu Refugee Camp. Data were collected using a structured, interviewer-administered questionnaire and medical chart review based on a standard checklist. The Patient Health Questionnaire-9 (PHQ-9) was used to assess depression. Data were coded and entered into EpiData version 4.6.0.6 and analyzed using SPSS version 23. Descriptive statistics and bivariate and multivariable binary logistic regression analysis were performed. Variables with a p-value less than 0.05 in the final model were considered statistically significantly associated with depression.ResultsA total of 380 study participants took part in the study, with a response rate of 99.4%. More than half of the study participants (58.2%) were female, and the mean age of respondents was 32.71 (SD=7.42). The prevalence of depression among the displaced South Sudanese population living with HIV/AIDS in the Ethiopia Okugu Refugee Camp was 56.8% (95% CI: 51.8%–61.9%). Female sex (AOR = 2.6; 95% CI: 1.24, 6.28), opportunistic infections (AOR = 3.00; 95% CI: 1.75, 7.06), a CD4 count < 200 cells/mm3 (AOR = 2.40; 95% CI: 1.78, 8.23), and poor social support (AOR = 4.70; 95% CI: 1.98, 9.79) were significantly associated with depression among the refugees.ConclusionsThe magnitude of depression among refugees living with HIV/AIDS was significantly high. Therefore, regular screening of people living with HIV for depression through integration of mental health services with routine ART services and equipping healthcare providers with essential supplies to deal with the problems of refugees are crucial.